Analisis Kompetensi Dasar Esensial pada Mata Pelajaran Sejarah Indonesia di Masa Pandemi Covid-19 - Asyrul Fikri; Anju Nofarof Hasudungan (Indonesian Journal of Social Science Education (IJSSE), 2021)
This study aims to describe the results of the analysis of the essential basic competencies of Indonesian history subjects in the emergency curriculum period based on the principles of UKRK (Urgency, Continuity, Relevance, Usability). The syllabus used by Indonesian history teachers at the beginning of the pandemic and in the transition after the issuance of Keputusan Menteri Pendidikan dan Kebudayaan Republik No 719/P Tahun 2020 still uses the syllabus made during the conditions before Covid-19. As a result, learning Indonesian history sourced from the syllabus is irrelevant to current conditions.This research uses descriptive qualitative research. Data collection was carried out by means of observation, document analysis, interviews, and literature study. The results showed that the Basic Competence (KD) contained in the previous syllabus was a collection of KD made with normal living conditions. The Covid-19 pandemic has forced the learning pattern that was originally in the classroom to change to Distance Learning (PJJ). So, KD in normal conditions syllabus is still used, so this is irrelevant and very difficult for students. Therefore, this study recommends the results of essential KD analysis in compulsory history subjects. So that it can be used by history teachers throughout Indonesia.